FACTORS RELATED TO COMPLIANCE WITH MEDICAL NUTRITION THERAPY IN DIABETES MELLITUS PATIENTS - Tutik Ernawati; Dian Isti Angraini; Harmaina (Majalah Kedokteran Sriwijaya, 2024)
Diabetes mellitus is a chronic disease that is increasing over time. The success of treatment and prevention of diabetes mellitus progression is influenced by patient compliance in taking medication and nutritional therapy as an effort to maintain blood glucose levels within the normal range. The aim of this research is to determine the factors associated with compliance with medical nutrition therapy in diabetes mellitus patients. This research is an analytical observational study with a cross sectional approach. This research was conducted from April to October 2023. The research sample was 95 DM patients in the Kalirejo Public Health Center working area., Pesawaran, Lampung. Samples were taken using a purposive sampling technique that met the inclusion and exclusion criteria. Data on knowledge, education, age and income were collected using a questionnaire, as well as data on compliance with medical nutrition therapy was assessed by comparing nutritional intake with the nutritional needs of DM patients based on a 2x24h food recall questionnaire. Data were analyzed using chi square and logistic regression. The results of the study showed that non-compliance with medical nutritional therapy for DM patients was 80%. Knowledge, education, age, and income are related to compliance with medical nutritional therapy for DM patients (p=0.048; p=0.02; p=003; p=0.002). Compliance with medical nutritional therapy for DM patients is very necessary in controlling blood sugar in order to prevent complications.